(untitled) (Research, Society and Development, 2022)
From the characterization of the soil hydrodynamics, there are subsidies for an adequate management of the area, whether rainfed or irrigated in semiarid regions, studies in this line of research have been very scarce and have been leading many areas to the degradation process, compromising production. The objective of this research was to evaluate the hydrodynamic parameters of the soil, in addition to identifying the possible need for soil drainage in an area undergoing environmental recovery. The experimental area is located in the municipality of São José dos Cordeiros - PB located in Cariri Paraibano. Ten soil samples were taken to evaluate the physical parameters at a depth of 30 cm. Analyzes were performed in the irrigation and salinity laboratory. The saturated hydraulic conductivity (K0) by the inverse Auger Hole method (Porchet), performed in the field. The soil has a loam, sandy clay loam and sandy loam texture, the soil density values ranged from 1.30 to 1.61 g cm-3, for particle density the variation was 2.68 to 2.72 g cm- 3. The saturated hydraulic conductivity of the soil ranged from 0.39 to 1.5 m.day-1 in the area, being classified as slow and moderate. The drainable porosity ranged from 31.28 to 42.79.